PEComa-A Rare Uterine Neoplasm: A Case Report - R Padmehr; S Arasteh; S Aminimoghaddam; A Rahbari; M Bohloli; SM Mir Eskandari; H Mohabbat Dar; M Ahmad Beigi; N Talebi Biderouni (JRI, 2022)
Background: Perivascular Epithelioid Cell Tumors (PEComas) are rare mesenchymal tumors originating from perivascular epithelioid cells. The second common affected organ is uterine. Most of PEComas are benign and patients have good prognosis. At the present time, surgery is the main treatment and adjuvant chemotherapy is used in malignant cases, although the best diagnostic and management method is yet to be discovered considering the rarity of this neoplasm. Case Presentation: The patient was a 53 year old lady with a history of two vaginal deliveries and no previous surgery. She had severe pelvic pain and underwent MRI with the primary impression of sarcoma. In MRI, she had a 7 cm mass in lower segment of uterus. The patient underwent laparoscopic hysterectomy, bilateral oophorectomy, lymphadenectomy, and omental biopsy in Jam Hospital. Pathologic report of the patient revealed malignant PEComa without lymph node and omentum involvement. Conclusion: Diagnosis of PEComa before surgery is difficult and its differential diagnoses form uterine leiomyoma or leiomyosarcoma. Final diagnosis can be made after surgical biopsy and immunohistochemistry evaluation. Surgery is still the main treatment and adjuvant therapy is used in high risk patients.